Pengelolaan Pembelajaraan Kimia Berbasis Multimedia (Studi Situs SMA Negeri Karangpandan) - Rochani, Prastiwi Idha, Prof.Dr.Budi Murtiyasa, M.Kom, Dr. Sofyan Anif, M.Si (2016)
The objectives of this study are: (1) to describe Multimedia -based Chemistry lesson plans Site Study of SMA NegeriKarangpandan ; (2) to describe the implementation of Multimedia -based Chemistry learning Site Study of SMA Karangpandan; and (3) to classify the learning evaluation of Multimedia -based Chemistry learning Site Study of SMA Karangpandan. The method used in this study is qualitative. The research design is Ethnographic research. The data collections were collected by using interview, observation, and document analysis. The data were analyzed through: (1) flow model of analysis and (2) an interactive model. The validity of the data used triangulation, i.e. source triangulation, technique triangulation, and time triangulation. The results of the research are: (1) chemistry lesson plan was conducted by each teacher to identify the problems in chemistry lesson and the time allotment. Based on the problem identification, chemistry lesson plan was madeby the teacher based on competency standards and basic competencies in the chemistry curriculum. The result of the research concluded that not all of basic competencies were planned by using multi media. The Multimedia - based lesson plans were implemented in accordance with the teacher ability and student needs; (2) in the learning implementation not all the teachers used multimedia because some of them did not have capability in applying multimedia as teaching aids. The use of multimedia in chemistry lesson was limited to the operation of CD and to the presentation of Power Point; and (3) the evaluation was conducted before and after teaching and learning process in order to know the level of students' abilities. Evaluation process conducted by the teacher was the use of the Internet as a source of student learning. While, the result evaluation conducted by the daily tests, midterm test and semester test was used to determine learning outcomes.Learning outcome evaluation conducted by the teacher was used to promote to the next grade.